Upaya Pelestarian Ekosistem Pesisir oleh Mahasiswa KUKERTA MBKM dengan Mengadakan Pembibitan dan Penanaman 1000 Mangrove di Desa Buruk Bakul - Prianto, Eko; Akmal, Muhammad; Sari, Intan Purnama; Dewi, Yuni Sukma; Pranata, Eka; Lubis, Najiyya Sahilda; Utami, Tiara; Desvind, Elfahra Dyta Putri; Saputri, Ratih Okta; Ramadhani, Wahyu Ikma; Situmorang, Icha Regina (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Mangroves are tropical trees that thrive in conditions intolerable to most woody species: saline, coastal waters subjected to relentless tidal fluctuations. Due to their significant carbon sequestration capacity, mangroves serve as a crucial weapon in the battle against climate change, yet they face global threats. By protecting mangrove forests, we can contribute to safeguarding our planet's future.The mangrove forest in Buruk Bakul village exemplifies a well-preserved mangrove ecosystem in Indonesia. Situated along the coast, this forest acts as a natural barrier, protecting the village from coastal erosion and saltwater intrusion. In 2024, the MBKM  Community Service Program (Kuliah Kerja Nyata) at the University of Riau implemented a project to cultivate and plant 1,000 mangrove trees in Buruk Bakul Village. This initiative aims to restore the mangrove ecosystem, enhance community awareness about environmental conservation, and provide students with practical experience in environmental conservation efforts.Therefore, a collaborative approach involving government agencies, local communities, and various stakeholders is essential to sustainably preserve and manage the mangrove forest in Buruk Bakul village.